Penerapan Model Pembelajaran Problem Based Learning Berbasis Kearifan Lokal Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Zat Aditif - Agnes Juniar Arrozaqu; Beni Setiawan (PendIPA Journal of Science Education, 2022)
The purpose of this research is to describe the implementation of the learning process, improving learning outcomes and student responses by using Problem Based Learning model based on a local wisdom science class of second grade at junior high school. The type of research used a Pre-experimental design and the research design used One Group Pretest-Posttest Design. This research was implemented to students in class VIII-G as many as 34 students at Junior High School 34 Surabaya in the 2021/2022 academic year. Data collection techniques were using tests, questionnaires, and observations. The instruments of this research are test sheets in the form of pretest and posttest, student response questionnaires observation sheets. The implementation of learning using the Problem Based Learning model based on local wisdom has an average assessment at the first meeting obtained a percentage of 94.31% and the second meeting 100%. Learning outcomes can be seen in the increase of pretest and posttest which get average N-Gain scores of 0.69 which included the moderate category. Then the results of the effect size analysis show that the effectively of the Problem Based Learning model based on local wisdom is 3.20 with a strong effect. The students gave a positive response to the application of the Problem Based Learning model based on local wisdom with an average percentage of 97,93%. The conclusion of this research is the application of the Problem Based Learning model based on local wisdom can improve student learning outcomes.